ETUDE COMPARATIVE DE LA STRUCTURE DIAMETRIQUE DE L’ESSENCE DIOSPYROS CRASSIFLORA HIERN (EBENACEAE) DANS LES DISPOSITIFS PERMANENTS DE LA RESERVE FORESTIERE DE YOKO ET DE LA FORET DE BIARO (UBUNDU, R.D. CONGO). - Lomba, Christophe B.; BONGINDA, E (IJRDO-Journal of Applied Science, 2022)
Study of diameter structure of Diospyros crassiflora specie had been affected in Yoko Forest Reserve and Biaro Forest into two permanent dispositives of 400 ha each one. This work has objectives based on density distribution by diameter class and pedologic parameters in two sits. Al stems of dbh ³ 10 cm studied specie have been inventoried, measured through 40 bands of 10 ha by one and pedologic parameters in two sits. 519 trees have been counted with 325 have been inventoried in Biaro forest. This one present a good reconstitution of stems specie for have much individuals into inferior diameters classes. Pedologic analysis had realized and presented in two sits acid soils.